The Hunsrück biota: A unique window into the ecology of Lower Devonian arthropods. Issue 2 (March 2016) - Rust, Jes; Bergmann, Alexandra; Bartels, Christoph; Schoenemann, Brigitte; Sedlmeier, Stephanie; Kühl, Gabriele
Abstract: The approximately 400-million-year old Hunsrück biota provides a unique window into Devonian marine life. Fossil evidence suggests that this biota was dominated by echinoderms and various classes of arthropods, including Trilobita, stem lineage representatives of Euarthropoda, Chelicerata and Eucrustacea, as well as several crown group Chelicerata and Eucrustacea. The Hunsrück biota's exceptional preservation allows detailed reconstructions and description of key-aspects of its fauna's functional morphologies thereby revealing modes of locomotion, sensory perception, and feeding strategies. Morphological and stratigraphic data are used for a critical interpretation of the likely habitats, mode of life and nutritional characteristics of this diverse fauna. Potential predators include pycnogonids and other chelicerates, as well as the now extinct stem arthropods Schinderhannes bartelsi, Cambronatus brasseli and Wingertshellicus backesi . Mainly the deposit feeding Trilobita, Marrellomorpha and Megacheira, such as Bundenbachiellus giganteus, represents scavengers. Possibly, opportunistic scavenging was also performed by the afore-mentioned predators. Most of the studied arthropods appear to have been adapted to living in relatively well-illuminated conditions within the photic zone. Fossil evidence for associations amongst arthropods and other classes of metazoans is reported. These associations provide evidence of likely community structures. Highlights: Analysis of the lower Devonian Hunsrück Lagerstätte provides data about the former range of taxa and their ecological affinities. Stratigraphic and geological analyzes suggest that the ancient Hunsrück seas were within the photic zone. Most studied taxa had eye morphologies suited for life within the shallow waters, as suggested by Paleobathymetric data.